Numerical Analysis of Energy Loss in Stall Zone for Full Tubular Pump Based on Entropy Generation Theory - Lijian Shi; Yuhang Jiang; Wei Shi; Yi Sun; Fengquan Qiao; Fangping Tang; Tian Xu (Journal of Marine Science and Engineering, 2023)
As a low-head and non-drive pump, the head reduction and stall advance are the key factors that restrict the popularization and application of the full tubular pump (FTP). In this paper, the shear stress transport (SST) k-ω turbulence model is used for the numerical calculation of the FTP. Additionally, based on the entropy generation theory, the energy loss and main distribution zones of the FTP under all working conditions are analyzed, and the mechanism of inducing its stall advance is explored. By comparison, we found that there is little difference between the numerical simulation results and the model test. Turbulence entropy generation has a high proportion under small flow conditions, which is mainly reflected in the outlet flow separation zone of the suction surface of the impeller blade, the guide vane inlet zone where inlet deviation exists, and the trailing edge of the guide vane where the flow separation exists. Compared with the axial flow pump (AFP), when the flow rate decreases, the clearance reflow between the stator and rotor induces the deterioration of the flow at the impeller inlet, and the turbulent entropy generation in the impeller channel increases rapidly, making the FTP enter the stall zone ahead of time. The clearance backflow affects the flow pattern of the inlet pipe, making the turbulence entropy generation in the outlet area of the inlet pipe increase. The total entropy generation in the stator–rotor region is little affected by the pump flow conditions, and it is mainly affected by different stator–rotor backflow clearance dimensions. This study can provide a reference for exploring the energy loss of the FTP and revealing its stall characteristics.